Surplus fat rapidly increases fat oxidation and insulin resistance in lipodystrophic mice - Amandine Girousse; Samuel Virtue; Dan Hart; Antonio Vidal-Puig; Peter R. Murgatroyd; Etienne Mouisel; Coralie Sengenès; David B. Savage (Elsevier, 2018)
Objective: Surplus dietary fat cannot be converted into other macronutrient forms or excreted, so has to be stored or oxidized. Healthy mammals store excess energy in the form of triacylgycerol (TAG) in lipid droplets within adipocytes rather than oxidizing it, and thus ultimately gain weight. The 'overflow hypothesis' posits that the capacity to increase the size and number of adipocytes is finite and that when this limit is exceeded, fat accumulates in ectopic sites and leads to metabolic disease. Methods: Here we studied the energetic and biochemical consequences of short-term (2-day) excess fat ingestion in a lipodystrophic (A-ZIP/F-1) mouse model in which adipose capacity is severely restricted. Results: In wildtype littermates, this acute exposure to high fat diets resulted in excess energy intake and weight gain without any significant changes in macronutrient oxidation rates, glucose, TAG, or insulin levels. In contrast, hyperphagic lipodystrophic mice failed to gain weight; rather, they significantly increased hepatic steatosis and fat oxidation. This response was associated with a significant increase in hyperglycemia, hyperinsulinemia, glucosuria, hypertriglyceridemia, and worsening insulin tolerance. Conclusions: These data suggest that when adipose storage reserves are saturated, excess fat intake necessarily increases fat oxidation and induces oxidative substrate competition which exacerbates insulin resistance resolving any residual energy surplus through excretion of glucose. Keywords: Lipodystrophy, Energy partitioning, Fatty acid oxidation, Substrate competition, Insulin resistance